(untitled) (Research, Society and Development, 2021)
The Ajuruteua beach (Bragança-Pará-Brazil) undergoes dynamic changes by the process of marine erosion, generating several environmental and quality of life, from local community, consequences. This study aimed to estimate by the Replacement Cost Valuation Method (MVCR) the economic losses generated directly and indirectly by water erosion, in the assistance of the beach management process and its tourist use by the public authorities. The adopted method employed questionnaires and checklists, applied to a sample of 81 establishments, to identify the costs of losses and recovery/reconstruction (total or partial) of the affected assets. The result obtained a general cost/loss in the order of R 4,165,000.00 linked to partial and/or total loss of properties, investments in restoration, reconstruction or relocation. And an average General Replacement Cost (CR) of R 6,325,889.40; indicating that socioeconomic losses can be admitted as significant and should be rethought in the sense of planning and coastal space management.